2016
DOI: 10.1371/journal.pone.0149519
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrofolate-Reductase Mutations in Plasmodium knowlesi Appear Unrelated to Selective Drug Pressure from Putative Human-To-Human Transmission in Sabah, Malaysia

Abstract: BackgroundMalaria caused by zoonotic Plasmodium knowlesi is an emerging threat in Eastern Malaysia. Despite demonstrated vector competency, it is unknown whether human-to-human (H-H) transmission is occurring naturally. We sought evidence of drug selection pressure from the antimalarial sulfadoxine-pyrimethamine (SP) as a potential marker of H-H transmission.MethodsThe P. knowlesi dihdyrofolate-reductase (pkdhfr) gene was sequenced from 449 P. knowlesi malaria cases from Sabah (Malaysian Borneo) and genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…In early PCR protocols, there was cross-reactivity with P. vivax , its closest phylogenetic relative among the human malaria parasites, but more-recent methods such as those used here are highly specific. As with P. cynomolgi, P. knowlesi is not under antimalarial drug selection pressure and so remains fully susceptible to all of the antimalarial drugs [33]. Although the number of subjects with asymptomatic nonhuman-primate malaria parasite infections recorded in this large survey was small, there was still a significant difference in the calculated parasite densities, with P. cynomolgi carried at lower parasitemia levels.…”
Section: Discussionmentioning
confidence: 99%
“…In early PCR protocols, there was cross-reactivity with P. vivax , its closest phylogenetic relative among the human malaria parasites, but more-recent methods such as those used here are highly specific. As with P. cynomolgi, P. knowlesi is not under antimalarial drug selection pressure and so remains fully susceptible to all of the antimalarial drugs [33]. Although the number of subjects with asymptomatic nonhuman-primate malaria parasite infections recorded in this large survey was small, there was still a significant difference in the calculated parasite densities, with P. cynomolgi carried at lower parasitemia levels.…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional structural models of the two mutant proteins in complex with pyrimethamine showed that both Arg34 and Thr105 are not part of the binding pocket and are located far from the inhibitor-binding site, suggesting that the mutation at residue 34 and deletion of residue 105 are not associated with pyrimethamine resistance. Other studies have found a number of pkdhfr mutations, including Arg34Leu from Sabah, Malaysia, with no signs of positive selection [ 38 ]. Moreover, ex vivo enzyme activity has also been studied, but there was no association with antifolate resistance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there was no evidence of selective drug pressure in humans. 70 In addition to crt and dhfr, other orthologs of P. falciparum drug resistance genes, including multidrug resistance-1 (mdr1), dihydropteroate synthase (dhps), and kelch K13, were also looked at, with no signs of positive selection. 71 Since only human hosts would be expected to have antimalarial drug exposure and as long as the transmission of P. knowlesi remains zoonotic, the absence of drug selection pressure will make it unlikely to develop antimalarial drug resistance.…”
Section: Treatment and Drug Resistancementioning
confidence: 99%